2017
DOI: 10.1039/c6sc04866h
|View full text |Cite
|
Sign up to set email alerts
|

Expedient synthesis of the heneicosasaccharyl mannose capped arabinomannan of the Mycobacterium tuberculosis cellular envelope by glycosyl carbonate donors

Abstract: Herein, a highly convergent strategy is developed to synthesize heneicosasaccharyl arabinomannan for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 47 publications
1
26
0
1
Order By: Relevance
“…The glycosidation between diol 8 and acceptor 32 was performed affording an inseparable mixture of pentasaccharides 35 . Earlier reports on the synthesis of pentasaccharide motifs indicated that the diastereomeric ratio would likely result from the C‐5 position of the aglycon due to its inherently more reactive nature compared with the C‐3‐OH . Temperature controlled glycosidations and reversing the addition sequence of glycosyl donor and acceptor did not improve the diastereoselectivity and, more frustratingly, the isomers could not be separated.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The glycosidation between diol 8 and acceptor 32 was performed affording an inseparable mixture of pentasaccharides 35 . Earlier reports on the synthesis of pentasaccharide motifs indicated that the diastereomeric ratio would likely result from the C‐5 position of the aglycon due to its inherently more reactive nature compared with the C‐3‐OH . Temperature controlled glycosidations and reversing the addition sequence of glycosyl donor and acceptor did not improve the diastereoselectivity and, more frustratingly, the isomers could not be separated.…”
Section: Resultsmentioning
confidence: 87%
“…Now,t he stage was set for the gold/silver-catalysed glycosidation in a{ 2 2 + 1} fashion.T he glycosidation between diol 8 and acceptor 32 was performed affording an inseparable mixture of pentasaccharides 35.E arlier reports on the synthesis of pentasaccharidem otifs indicated that the diastereomericr atio would likely result from the C-5 position of the aglycon due to its inherently more reactive nature compared with the C-3-OH. [18,[21][22][23] Temperature controlled glycosidations and reversing the addition sequence of glycosyl donor and acceptor did not improvet he diastereoselectivity and, more frustratingly, the isomersc ould not be separated. Hence, sequential addition of the disaccharide was investigated and installation at the C-5 positionp rior to the C-3 positionw ould be beneficial because the mixtureo fc ompounds, if any,w as expected to be easy to purify.W ith this idea, orthoester 33 was saponified, monosilylated using 1.1 equivalent of TBDPS-Cl at 0 8Ca nd installation of the levulinoate protectionw as carried-out at the C-3 position to afford 36 in 61 %o ver three steps.…”
Section: Synthesis Of Pentaarabinofuranosyl Donormentioning
confidence: 95%
See 1 more Smart Citation
“…The regio‐ and stereochemical issues are major challenges during glycans synthesis, and results in a time‐consuming and tedious process for carbohydrate synthesis . Indeed, examples of the synthesis of long, branched, and complex carbohydrate chains with over 15 units are still limited . Therefore, development of efficient strategies for the assembly of long, branched, and complex carbohydrate sequences is direly needed and remains one of the most challenging tasks for synthetic chemists.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Indeed, examples of the synthesis of long,b ranched, and complex carbohydrate chains with over 15 units are still limited. [13][14][15][16][17][18][19][20] Therefore, development of efficient strategies for the assembly of long, branched, and complex carbohydrate sequences is direly needed and remains one of the most challenging tasks for synthetic chemists.…”
Section: Introductionmentioning
confidence: 99%